Co-Occurrence of Pseudopregnancy, Pyometra, and Bacterial Parasitic Anaplasmosis in a Persian Cat - Budiono, Novericko Ginger; Rahmiati, Dwi Utari; Tuliman, Nurul Annisa; Delimasari, Zahrizada Zamrudina; Murtiningrum, Fitria Senja; Adistya, Erly Rizka; Nugraha, Arifin Budiman; Silvarajoo, Keertana; Milna, Resi (The International Journal of Tropical Veterinary and Biomedical Research, 2023)
An intact female tabby Persian cat, 26-month-old, was brought to IPB University Veterinary Teaching Hospital on the 21st of February, 2023, due to vaginal discharge, inappetence, and lethargy. Physical examination revealed a distended abdomen, mammary gland enlargement, and fever (40.1 C). The heart and respiratory rates were 128 beats per minute and 32 times per minute, respectively. The patient body weight was 3.87 kg. The veterinarian palpated masses inside the abdominal cavity and observed obvious purulent and haemorrhagic vaginal discharge. Haematology showed leukopenia and thrombocytopenia, and the eosinophil percentage of white blood cells was increased (eosinophilia). Blood chemistry analysis showed hyperglycaemia. Ultrasonography showed two hyperechoic masses inside two hypoechoic pouches in the queens uterus, suspected as two dead foetuses (no heartbeat). Roentgen revealed abnormalities in the vena cava caudalis, bronchial pattern in the lung, radioopaque masses in the ventral abdomen, radio-opacity changes in the small and large intestines, and abnormalities in the spleen. The patients diagnosis was pyometra, and ovariohysterectomy surgery was performed on the patient. The patient was treated with additional medicines (antibiotics and others) according to the symptoms. The patients symptoms disappeared, except for the fluctuating febrile and pale mucous membrane. A blood smear performed on the 1st of March 2023 revealed Anaplasma phagocytophilum (A. phagocytophilum) in the white blood cells, and immediately doxycycline treatment (10 mg/kg body weight, twice daily) was given. The patient was discharged from the hospital on the 14th of March, 2023, with no febrile or other symptoms reported. This case is the first report of open cervix-type pyometra and anaplasmosis co-occurrence in a Persian cat from IPB University Veterinary Teaching Hospital in Indonesia.